Relationship between age, osteoporosis and coronary artery calcification detected by high-definition computerized tomography in Chinese elderly men. (November 2018) - Liu, Yuan; Fu, Shihui; Bai, Yongyi; Luo, Leiming; Ye, Ping
Highlights: The relationship between bone mineral density (BMD) and coronary artery calcification (CAC) in older men remains subject to debate. The present study was designed to evaluate the age-related acceleration of osteoporosis and CAC in Chinese elderly men. In this study, age was found to be an important factor for loss of BMD; no relationship was observed between osteoporosis and CAC in elderly men. Abstract: Background: Few studies have analyzed the relationship between bone mineral density (BMD) and coronary artery calcification (CAC) in older men, and it remains subject to debate. The present study was designed to evaluate the age-related acceleration of osteoporosis and CAC, as well as the relationship between BMD and CAC in Chinese elderly men. Methods: Participants included 120 men older than 60 years. CAC was measured with high-definition computerized tomography. It is a highly sensitive technique for detecting the CAC and provides the most accurate CAC scores up to date. Results: Mean (standard deviation) age was 73 (8.5) years. For osteoporosis, there was a strongly inverse correlation between age and BMD of all scanned body parts (p < 0.05 for all) except the lumbar spine 1–4 (p > 0.05 for all). For CAC, there was a moderately positive correlation of agatston, volume and mass scores with age. CAC was present in 67% of participants. There was no significant correlation between all kinds of CAC scores including agatston, volume and mass scores, and BMD of all scanned body parts including lumbar spine 1–4, femoral neck, femoral trochanter and total femur (p > 0.05 for all). BMD of all these body parts had no ability to identify the CAC (p > 0.05 for all). Furthermore, on multiple linear regression analysis, the relationship between CAC scores and BMD remained statistically non-significant. Conclusions: Age constituted an important factor common for loss of BMD and development of CAC detected by HDCT, and no direct relationship was observed between osteoporosis and CAC in Chinese elderly men.